Nano kaolin clay as bitumen modifier for sustainable development: Part B - Putra Jaya, Ramadhansyah; Masri, K. A.; Mudjanarko, Sri Wiwoho; Setiawan, Muhammad Ikhsan (Elsevier Inc., 2022)
This chapter presented the continued investigation outlined in Part A: Effectiveness and Efficiency of Nano Kaolin Clay as Bitumen Modifier. The asphalt binder incorporating nanoclay was tested in the unaged and aged condition to simulate the pavement condition during service life.